Case Study and Analysis of Patients with Acute Myocardial Infarction in Intensive Care Unit of Pare Hospital - Latdhivongsakorn, Vichien (Journal of Health Science of Thailand, 1994)
Clinical data from 109 patients diagnosed as acute myocardial infarction admitted in ICU and Sub-ICU units of Prae Hospital between January 1989 to January 1992 were studied and analysed. There were 45 male patients and 64 female patients. The average age was 63.08 years old (32-94). There were 14 patients died in the hospital. In-hospital mortality rate was 12.84%. Most of them died from cardiogenic shock. Age and severity of congestive heart failure on the admission day were the important mortality indices. There was no statistically signiﬁcant in the mortality rate between Q and non-Q wave infarction in the hospital. Seventy-nine patients who survived had been followed-up for 1 year and the mortality rate was 10.13%. Good timing for discharage was 6 days after admission.